NEW DESIGN METHOD FOR MAIN-AUXILIARY MODEL CONSTANT SPRINF SUPPORT HANGER - XING QingGuo; YANG LuLu; GANG XianYue; CHU ZhenMei (Jixie qiangdu)
The constant spring support hanger is usually used for supporting the conveying pipeline and it can abstain additional stress when the conveying pipe had vertical displacement. The knife-type cam is the core component of the constant spring support hanger.The design accuracy of the cam curve has direct influence on the work load deviation of the constant spring support hanger. According to the Instant relationship between the outside force and the spring energy changes in the body coordinate system,The elliptic algebra Equation of cam rotation angle and load tube vertical displacement was derived by using energe method. The cam design formula was put forward through the transformation of the global coordinates and the body coordinate. Considered the actual structure of the constant spring support hanger,the cam curve formula considering the radius of the roller is derived. The comparative analysis shows that the design accuracy of the cam curve equation established in this paper is better than the traditional method. Considered the influence of the roller radius can improve the support constant of the constant hangers.